Effect of the signaling lymphocytic activation molecule (SLAM) in the modulation of T cells in immune response to Leishmania braziliensis in vitro - Coêlho, Zirlane Castelo Branco; Teixeira, Maria Jania; Vilar, Maria do Livramento Leitão; Matos, Jesamar Correia; Matos, Jesamar Correia; Coêlho, Ivo Castelo Branco; Andrade, Geanne Matos; Pompeu, Margarida Maria Lima (Journal of Health & Biological Sciences, 2017)
Introduction: Signaling lymphocyte activation molecule (SLAM) is a self-ligand receptor on the surface of activated T- and B-lymphocytes, macrophages, and DC. Studies have shown PBMC from healthy individuals exposed to Leishmania differ in IFN-γ production. Objective: We investigated the role of SLAM signaling pathway in PMBC from high (HP) and low (LP) IFN-γ producers exposed to L. braziliensis in vitro. Methods: PBMC from 43 healthy individuals were cultured with or without antigen, α-SLAM, rIL-12 and rIFN-γ. The cytokines production was evaluated by ELISA, and SLAM expression by flow cytometry. Results: L. braziliensis associated with rIFN-γ or rIL-12 reduced early SLAM but did not modify this response later in HP. α-SLAM did not alter CD3+SLAM+ expression, and not affected IFN-γ and IL-13 production, in both groups, but increased significantly IL-10 in HP. Leishmania associated with α-SLAM and rIL-12 increased IFN-γ in LP, as well as IL-13 in HP. LP group presented low IFN-γ and IL-13 production, and low SLAM expression. Conclusion: Collectively, these findings suggest that when PBMC from healthy individuals are sensitized with L. braziliensis in vitro, SLAM acts in modulating Th1 response in HP individuals and induces a condition of immunosuppression in LP individuals.